OCCUPATIONAL BURNOUT COPING AND HOBBY: TEACHER’S SURVEY DATA - Merkys, Gediminas; Bubelienė, Daiva (Acta Paedagogica Vilnensia, 2013)
This article presents quantative survey data on Lithuanian teachers (N = 961). The geography of this survey includes almost all country’s administrative units, and its data are approaching the requirements of a representative survey. Concepts and empirical research traditions in terms of a survey are related to work stress and occupational burnout research, as well as lifestyle, leisure, and hobby studies. The answer was sought to the question, whether a hobby (especially that related to the high levels of physical activity) has an influence on the mitigation of occupational burnout symptoms. A one-dimensional psychometric scale was set up to measure the dependent variable (occupational burnout), which consists of 39 primary indicators and is characterized by a very high reliability performance. The study has shown that possessing a hobby, regardless of its connection with physical activity, has a significant influence on the reduction to occupational burnout symptoms. Teachers who have a hobby and are regularly engaged in it have significantly less expressed symptoms of burnout than those who have no hobbies at all, or do have but are little involved in it or are engaged in a hobby very rarely. This article names the further directions of relevant researches. It focuses a discussion and recommendations: a) to develop focuses on educational environments in higher education, which would allow to form a hobby for future specialists, b) to develop the recreational infrastructure at universities and schools as in socially responsible organizations, c) to give the status of public value to teachers’ leisure organization and to support this activity.
Keywords: teachers; occupational burnout; work stress; hobby; leisure